Studi Kasus Forensik Pada Luka Trauma Tumpul Ditinjau Dari Perspektif Medikolegal - Haifa Ayu Dinarsono Putri; Rahmadsyah Rahmadsyah (Jurnal Anestesi, 2025)
Violence reflects social conflicts that can harm both the physical and psychological well-being of victims while violating legal norms. Although physical crime trends in Indonesia showed a decline from 2017 to 2019, North Sumatra remained the epicenter of violence incidents, particularly assault cases. The handling of such cases is inseparable from the role of Visum et Repertum, a legal document that serves as key evidence in the criminal justice process, as stipulated in Article 184 of the Indonesian Penal Code (KUHP). Through a case study of a 69-year-old man who became a victim of minor assault, this study highlights the process of medical investigation and legal analysis. A bruise on the head caused by a bare-handed blow did not hinder daily activities, classifying it as a minor assault punishable by up to three months in prison under Article 352 (1) of the Penal Code. This study emphasizes the need for synergy between controlling socio-economic factors and enforcing legal procedures to address violence, while strengthening the role of Visum et Repertum as a vital element of justice